Fine Tuning The Young Learners For Competitive Programming And Employability - et. al., S Suprakash, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Nowadays employability of graduating engineers has become very difficult. Most of the students go for a less paid job even which may not be in the proper field of study. Most of the high paying companies are looking for skilled people where the training that they have to provide is minimal no training have to be given. Most companies started recruiting people who scored best in competitive programming done through different media. This work studies the level of preparedness of students to face such competitive programing environment, where they need improvements and how this can be provided to the students through a unified platform. Competitive programming needs a lot of practice which is a key to success, and the components which are most required are discussed here.